6LoWPAN based wireless sensor networks - Krishnan Gopinath Shobha (2017)
Internet of Things (IoT) is rapidly growing and exploited in almost all the fields such as industrial automation, building automation, smart metering, smart homes etc. IoT is formed mostly from heavily resource constrained and low-cost tiny sensor devices. These devices are battery powered and have memory constraints. 6LoWPAN (IPv6 over Low-Power Wireless Personal Area Networks) is one of the most exciting protocols developed for IoT. 6LoWPAN allows these tiny sensor devices of low-power applications to connect to IPv6 networks. Because of 6LoWPAN, IPv6 packets can be sent over low-power and lossy (IEEE 802.15.4) networks. The IPv6 address space can address trillions of these tiny devices in IoT. Thus, the exhausting IPv4 addresses pool and almost infinite number of unique addresses provided by IPv6 space proves 6LoWPAN to be indispensable. Every node in the network becomes IP addressable and the wireless sensor network is connected to the real IP world. The network formed by the resource constrained devices specified above are low-power and lossy networks (LLN). Thus, LLN have limited power resources and are characterized by lossy links. The routing protocol designed for such IPv6 LLN is called RPL- ‘IPv6 Routing over Low-power and Lossy Networks’. RPL builds the network based on its defined ‘objective function’. In this dissertation, a 6LoWPAN based wireless sensor network application is implemented. The application is to capture CO2 levels in air along with other relevant parameters to know the indoor air quality (IAQ). The setup allows the data to be sensed and displayed in real time. It is developed from Instant Contiki OS. As these sensor devices used in 6LoWPAN networks are highly power constrained, the second objective of the project is to investigate and implement a more energy efficient routing by RPL. A new objective function is implemented based on fuzzy logic. This aims to reduce the energy consumption of the network. Cooja simulator from Contiki OS is used for this RPL implementation.